Pengaruh Model Pembelajaran Artikulasi Terhadap Keaktifan Belajar PAK Siswa Kelas X SMK Yayasan Soposurung Balige Kabupaten Toba Tahun Pembelajaran 2023/2024 - Basar Sitanggang; Tianggur Medi Napitupulu; Dame Taruli Simamora (Jurnal Riset Rumpun Agama dan Filsafat, 2023)
The aim of this research is to find out whether there is a positive and significant influence of the articulation learning model on the learning activeness of class The method used in this research is quantitative descriptive. The population is all 59 class Data was collected using a closed questionnaire with 30 items and all of them were positive. The results of data analysis show that there is a positive and significant influence of the articulation learning model on the learning activeness of class (=0.05,n=59) = 0.254, thus it is known that there is a positive relationship between variable n-2=57)= 2,000, thus there is a significant relationship between variable b) Regression coefficient of determination test (r2) = 25.3%. 3) Test the hypothesis using the F test to obtain Fcount > Ftable=(=0.05, dk numerator k=21, dk denominator=n-2=59-2=57) namely 19.30 > 1.39. Thus Ha is accepted and H0 is rejected.